Prediction of Carbamazepine-Succinic Acid Co-Crystal Dissolution in Ethanolic Solution using a Computational Molecular Dynamic Simulation Technique - Anuar, Nornizar; Sazmira Pauzi, Noor; Nurul ‘Ain Yusop, Siti; Salwani Md Azmi, Nik; Abd Rahim, Syarifah; Fitri Othman, Muhammad (International Journal of Engineering and Technology, 2018)
Carbamazepine (CBZ) is an anti-epileptic Class II drug according to the biopharmaceutical classification system and it forms a co-crystal with succinic acid (SA). The physicochemical properties of co-crystal are of interest since they control how the co-crystal behaves in different environment. In this study, the morphology of carbamazepine-succinic acid (CBZ-SA) co-crystal was predicted by applying the atomic charge calculated from MOPAC and DMol3 while the dissolution behavior of CBZ-SA in ethanol  was investigated using dynamic simulation by considering the transport properties of both co-crystal and solvent. The predicted CBZ-SA morphology shows a plate-like shape with the main crystal facet of (1 0 -1), (1 0 1), (1 1 0), (0 1 1), (0 1 0), (2 0 0) and (0 0 2). Attachment energy calculation shows that facet (1 0 -1) is the slowest growing facet having the lowest attachment energy of -27.91 kcal/mol, while facet (0 1 1) is the fastest growing facet with the highest value of attachment energy of -96.74 kcal/mol. The dissolution behavior of CBZ-SA in ethanol was also assessed through the mean square displacement (MSD) and diffusion coefficient calculation, and the result shows that the dissolution of co-crystal first occurs at facet (1 0 1) and last to dissolve at facet (1 1 0). Because the molecular configuration of the molecules at facet (1 0 1) leaves a large gap between molecules that makes it easier for the solvent molecules to penetrate the surface layer and the hydrophilic part of CBZ and succinic acid molecules is exposed to the surface forming hydrogen bond. Calculation of binding energy shows that the interaction of ethanol was more favorable at facet (1 1 0) with the value of -745.631 kcal/mol. The analysis carried out in this work showed that there is a promising relationship between RDF and diffusion coefficient in predicting the diffused molecules from the surface of the facets, as both methods predicted the facets (0 0 2), (2 0 0) and (1 0 1) as among the top three facets dissolved into the ethanol  environment. Both MSD and diffusion coefficient also predict that facets (0 1 0) and (1 1 0) are among the last facets dissolved. However, the binding energy calculation does not show any apparent relationship to neither RDF nor diffusion coefficient.